1969
DOI: 10.1017/s030500410004514x
|View full text |Cite
|
Sign up to set email alerts
|

The scattering of surface waves by a vertical plane barrier

Abstract: In this paper we use a method due to Williams (l) to discuss the scattering of surface waves of small amplitude on water of infinite depth by a fixed vertical plane barrier extending indefinitely downwards from a finite depth.1. Introduction. In 1966 Williams (l) presented a new approach to the problem of the scattering of two-dimensional surface waves of small amplitude on water of infinite depth by a fixed vertical plane barrier extending from above the free surface to a finite depth. This problem had previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…For example, Faulkner [10,11] used the WienerHopf technique to study oblique water wave diffraction by a submerged plane vertical barrier as well as by a partially immersed vertical barrier and obtained the reflection coefficient in each case for large wave number. Jarvis and Taylor [12] pointed out an error of formulation in [ 11 ] involving the submerged barrier, which they corrected, thus obtaining asymptotically the reflection coefficient for large wave number by analysing an integral equation of the second kind with Cauchy kernel, to which the problem was reduced. The mathematical analysis in [10][11][12] appears to be rather cumbersome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Faulkner [10,11] used the WienerHopf technique to study oblique water wave diffraction by a submerged plane vertical barrier as well as by a partially immersed vertical barrier and obtained the reflection coefficient in each case for large wave number. Jarvis and Taylor [12] pointed out an error of formulation in [ 11 ] involving the submerged barrier, which they corrected, thus obtaining asymptotically the reflection coefficient for large wave number by analysing an integral equation of the second kind with Cauchy kernel, to which the problem was reduced. The mathematical analysis in [10][11][12] appears to be rather cumbersome.…”
Section: Introductionmentioning
confidence: 99%
“…Jarvis and Taylor [12] pointed out an error of formulation in [ 11 ] involving the submerged barrier, which they corrected, thus obtaining asymptotically the reflection coefficient for large wave number by analysing an integral equation of the second kind with Cauchy kernel, to which the problem was reduced. The mathematical analysis in [10][11][12] appears to be rather cumbersome. Later, Evans and Morris [3] utilized an approximate method involving the use of a one-term Galerkin approximation to the solutions of two appropriate integral equations to obtain very accurate upper and lower bounds for the reflection and transmission coefficients for all angles of incidence and wave numbers for the problem of oblique water wave diffraction by a fixed vertical barrier partially immersed in deep water.…”
Section: Introductionmentioning
confidence: 99%
“…The scattering of surface waves obliquely incident on partially immersed or completely submerged vertical barriers and plates in infinite fluid were investigated by Faulkner [1,2], Jarvis and Taylor [3], Evans and Morris [4], Rhodes-Robinson [5] and Mandal and Goswami [6]. Levine [7] considered the scattering of surface waves obliquely incident on a submerged circular cylinder.…”
Section: Introductionmentioning
confidence: 99%
“…Levine & Rodemich (1958) studied the case and showed that this problem has an exact but complicated solution, although they did not obtain the detailed solution. Jarvis (1971) solved the complementary problem of two identical semi-infinite barriers extending downwards from a point a beneath the surface, and he also obtained the curves of reflection and transmission coefficients as a function of frequency, barrier spacing, and submergence depth of barriers.…”
Section: Diffraction By Thin Barriersmentioning
confidence: 99%
“…They showed how highly accurate complementary bounds could be computed with relative ease. Recently, Soumen et al (2009) reinvestigated the two-barrier problem of Jarvis (1971). The solved a system of Abel integral equations by…”
Section: Diffraction By Thin Barriersmentioning
confidence: 99%